Racionalidade instrumental e mediação organizacional: um estudo sobre a percepção dos gestores da Caixa - Lima, Isabella Gonçalves de (2003)
The purpose of this dissertation is to identify and to analyze the perception of CAIXA managers, front the Company, having as reference, the concepts of Instrumental Rationality and Organizacional Mediation. lnitially, a Phenomenological Method was used as a way to defrne the questions that would have to be answered, from the practical experiences of management of this researcher, decurrent of the together existing relationship to the Market Managers ofthe Segment ofClients ofMiddle and High Income ofthe CAIXA ECONOMICA FEDERAL. After that, the theoretical framework, suitable to the sustaining of the object of research was defrned, structuralized in the concepts of Instrumental Rationality, including traces characteristic of the Behavioral Syndrome and the Organizacional Mediation mechanisms. A descriptive research was carried out to support the initial perceptions, together to the same publico It was concluded, under the perception of these managers. That subjects see themselves at the mercy of values of a market-centered society, assimilate such society's codes and are run by thern, regardless of the context of a public organization. On the organizationallevel, the ideological mediations appears as the most powerful subjugation mechanism, in the measure where the type of performance of the CAIXA provokes in its managers, pride, sense of utility and differentiation. In exchange, the employees seduced and submitted to such power, apply themselves to the attainment of organizational goals, of extended and recurrent forrn, strengthening the principIes of the instrumental rationality. Such a process is selfsufficient. UItimately, the question is: How can such historical trend be altered, so a true sense ofhuman relations can be retrieved?